Evaluation of toxic/protective effects of the essential oil of Salvia officinalis on freshly isolated rat hepatocytes - Lima, Cristóvão F. (2004)
For this study the essential oil (EO) of sage (Salvia officinalis L.) was isolated from air-dried vegetative aerial parts of the plants by hydrodistillation and analysed by GC and GC-MS. A total yield of 12.07 mg of EO per g of plant dry mass was obtained and more than 50 compounds identified. The major compounds were cis-thujone (17.4 %), alpha-humulene (13.3 %), 1,8-cineole (12.7 %), E-caryophyllene (8.5 %) and borneol (8.3 %). The EO fraction of sage tea was also isolated by partition with pentane and the respective components identified. The toxic and antioxidant protective effects of S. officinalis EO were evaluated on freshly isolated rat hepatocytes. Cell viability (LDH leakage), lipid peroxidation and glutathione status were measured in experiments undertaken with cells (suspensions of 1x106 cells per millilitre) exposed to EO alone (toxicity of the EO; t-BHP as positive control); and with cells exposed to EO and an oxidative compound (t-BHP) together (in EO protection evaluation; quercetin as positive control) for 30 min. The results show that the EO is not toxic when present at concentrations below 200 nl/ml; it was only at 2000 nl EO/ml that a significant LDH leakage and GSH decrease were observed indicating cell damage. In the range of concentrations tested, the EO did not show protective effects against t-BHP-induced toxicity.